Pengaruh Kompetensi dan Pengalaman Kerja Auditor Internal Terhadap Kualitas Audit Berdasarkan Artikel Terindeks Sinta - Ilham Saputra; Siti Mariam; Nisya Z Nurwulan Sari; Salwa Febriyanti; Rachmat Agus Santoso (CV. Ulil Albab Corp, 2024)
This study aims to examine the influence of competence and work experience of internal auditors on audit quality. Internal auditors play a crucial role in maintaining audit quality and internal controls within organizations. The study adopts a qualitative approach by analyzing articles from Sinta-indexed journals. The findings indicate that auditors with higher competence tend to produce better audit quality. It is explained that competence affects audit quality. However, work experience and ethics have no significant effect on audit quality.In conclusion, organizations should focus on developing the competence of internal auditors to enhance audit quality. By improving the competence of internal auditors, organizations can obtain more accurate and reliable audits.